A rich and bountiful harvest: key discoveries in plant cell biology - Cheung, Alice Y.; Cosgrove, Daniel J.; Hara-Nishimura, Ikuko; Jürgens, Gerd; Lloyd, Clive; Robinson, David G.; Staehelin, L. Andrew; Weijers, Dolf (The plant cell, 2022)
The field of plant cell biology has a rich history of discovery, going back to Robert Hooke’s discovery of cells themselves. The development of microscopes and preparation techniques has allowed for the visualization of subcellular structures, and the use of protein biochemistry, genetics, and molecular biology has enabled the identification of proteins and mechanisms that regulate key cellular processes. In this review, seven senior plant cell biologists reflect on the development of this research field in the past decades, including the foundational contributions that their teams have made to our rich, current insights into cell biology. Topics covered include signaling and cell morphogenesis, membrane trafficking, cytokinesis, cytoskeletal regulation, and cell wall biology. In addition, these scientists illustrate the pathways to discovery in this exciting research field.